Effects of Gasoline and Smoking on Lipid Profile and Liver Functions among Gasoline Exposure Workers in Iraq - Mohammed, Chinar M.; Al-Sulaivany, Bassim A.; Fattah, Yousif M.; Al-Habib, Omar A.M.; Haji, Mohammed Bassam (International Journal of Occupational Safety and Health, 2023)
Introduction: The rapid and recent rise in the pandemic of cardiovascular disease implies that the environment plays a significant role. Numerous biological systems, such as the cardiovascular, blood-forming organs, liver, and kidneys, can be affected by gasoline and smoking. Because filling station employees, repair service workers, gasoline truck drivers, and refinery workers are all at a greater risk of being exposed to gasoline fumes. Even though gasoline and smoking have been investigated for so many years, few studies have looked into the effects of gasoline exposure combined with smoking on a variety of physiological mechanisms. As a result, we propose that combining gasoline exposure with smoking is a risk factor for cardiovascular diseases and impaired hepatic function. Methods: The study included 95 male adult volunteers who worked with gasoline and were exposed to different fuel derivatives as study group and age and sex-matched seemingly healthy non-exposed people as the controls. Questionnaire interviews were used to collect socio-demographic data and a standard technique was used to collect the blood samples. The levels of cholesterol, HDL4, LDL-C, triglyceride, and VLDL were measured, as well as for liver enzymes ALP, AST, ALT, indirect bilirubin, direct bilirubin, and total bilirubin were measured. Results: Our data suggest that smoking with gasoline exposure causes an increase in total and bad cholesterol levels, as well as a significant shift concerning the control group in lipid profile and liver enzymes. the exposed group had higher levels of ALP, and AST and significantly increased. In the nonsmoker exposed group D-bilirubin decreased in comparison to the control and exposed smoker group. Conclusion: This research concluded that the liver enzymes (ALP, AST, ALT) were higher among workers who smoke and are exposed to gasoline than in control subjects, similarly, the bad cholesterol also increase. Therefore, people who smoke and are handled with gasoline are at a higher risk of having heart and hepatic diseases.